Is the inclusion of animal source foods in fortified blended food justified? - Noriega, Kristen (Kansas State University, 2014)
Fortified blended foods (FBF) are used for the prevention and treatment of moderate acute malnutrition (MAM) in nutritionally vulnerable individuals, particularly children. A recent review of current FBF recommended the addition of animal source food (ASF), in the form of whey protein concentrate (WPC), to FBF, especially corn soy blend. The justifications for this recommendation include the potential of ASF to increase length, weight, muscle mass accretion, and recovery from wasting, as well as improve the product protein quality and provide essential growth factors. Evidence was collected from the following four different types of studies: 1) epidemiological, 2) ASF versus no intervention or a low-calorie control, 3) ASF versus an isocaloric non-ASF, and 4) ASF versus an isocaloric, isonitrogenous non-ASF. Epidemiological studies consistently associated improved growth outcomes with ASF consumption; however, little evidence from isocaloric and isocaloric, isonitrogenous interventions was found to support the inclusion of meat or milk in FBF. Evidence suggests that whey may benefit muscle mass accretion, but not linear growth. Overall, there is little evidence to support the costly addition of WPC to FBFs. Further randomized isocaloric, isonitrogenous ASF interventions with nutritionally vulnerable children are needed.
Keywords: Animal source food; Fortified blended food; Protein; Whey protein concentrate; Child growth; Food aid; Nutrition (0570); Public Health (0573)